Nature of the copper-nitrosyl intermediates of copper nitrite reductases during catalysis. Issue 46 (27th October 2020) - Hough, Michael A.; Conradie, Jeanet; Strange, Richard W.; Antonyuk, Svetlana V.; Eady, Robert R.; Ghosh, Abhik; Hasnain, S. Samar
Abstract : Observation of side-on copper-nitrosyl intermediate and its confirmation by DFT during catalysis of copper nitrite reductases. Abstract : The design and synthesis of copper complexes that can reduce nitrite to NO has attracted considerable interest. They have been guided by the structural information on the catalytic Cu centre of the widespread enzymes Cu nitrite reductases but the chemically novel side-on binding of NO observed in all crystallographic studies of these enzymes has been questioned in terms of its functional relevance. We show conversion of NO2 − to NO in the crystal maintained at 170 K and present 'molecular movies' defining events during enzyme turnover including the formation of side-on Cu-NO intermediate. DFT modelling suggests that both true CuNO 11 and formal CuNO 10 states may occur as side-on forms in an enzymatic active site with the stability of the CuNO 10 side-on form governed by the protonation state of the histidine ligands. Formation of a copper-nitrosyl intermediate thus needs to be accommodated in future design templates for functional synthetic Cu-NiR complexes.